2020
DOI: 10.15376/biores.16.1.911-941
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement potential of modified nanofibrillated cellulose in recycled paper production

Abstract: The influence of nanofibrillated cellulose (NFC) was investigated as a reinforcing agent to improve strength properties of papersheets fabricated from recycled pulp fibers of mixtures of old newspapers, old magazines, and old corrugated cardboards. To determine the effects of the NFC on the mechanical and physical properties of the recycled pulp papers, cellulose nanofibrils (NFC) were isolated from wheat straw, pretreated chemically and enzymatically (NFC-OX), and then added to the bulk suspensions of paperma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Regarding natural ones, cellulose fibers, including micro and nanofibers, from different sources are used in most cases. The mechanical properties of recycled paper have been significantly improved by the addition of nanocellulose varying the sources, such as oil palm empty fruit bunches [25], corn stalks [26], wheat straw [27], wood [9], recycled pulp [28], hemp [29], and others. The addition of wood virgin pulp to recycled pulp to improve mechanical performance has been investigated [30], as well as the addition to different agro-waste, for example, rice straw [31].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding natural ones, cellulose fibers, including micro and nanofibers, from different sources are used in most cases. The mechanical properties of recycled paper have been significantly improved by the addition of nanocellulose varying the sources, such as oil palm empty fruit bunches [25], corn stalks [26], wheat straw [27], wood [9], recycled pulp [28], hemp [29], and others. The addition of wood virgin pulp to recycled pulp to improve mechanical performance has been investigated [30], as well as the addition to different agro-waste, for example, rice straw [31].…”
Section: Introductionmentioning
confidence: 99%
“…Mazhari Mousavi et al (2017) indicated that incorporating CMC as an additive to alter the rheological properties of NFC suspension, by decreasing the fiber-fiber interactions of NFC fibrils, thus reduces flocculation tendency of NFC suspensions; therefore, it enables uniform spreading of NFC at moderate solids content. The rheological behaviours of the evaluated nanofibrillated celluloses in this work were given in the authors' previous study (Tozluoğlu et al 2021). The periodate-oxidated samples exhibited lower viscosity than TEMPO and PINO oxidated samples, therefore the formulation was able to penetrate and uniformly spread on the substrate surface under high pressure.…”
Section: Physical Propertiesmentioning
confidence: 94%
“…For instance, González et al (2012) reported that the bulk addition of 3% NFC to bleached eucalyptus pulp suspension increased °SR as 61.1%. Furthermore, 23.3% increase in °SR was reported by Tozluoğlu et al (2021) after the bulk addition of 4% NFC to recycled pulp suspensions. The use of retention agents not only increases retention but also has positive effects on the mechanical properties by enhancing fiber-fiber bonding, thus proper selection and optimization of retention agents would be required.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation